Gegen den Strom : Erlebtes aus Leipzig unter Hitler und der Stasi; "...es war tatsächlich möglich ..." - Schmutzler, Georg-Siegfried 1915-2003 (Vandenhoeck & Ruprecht, 1992)
Erlebtes aus Leipzig unter Hitler und der Stasi